Intricate Distribution Patterns of Six Cytotypes of Allium oleraceum at a Continental Scale: Niche Expansion and Innovation Followed by Niche Contraction With Increasing Ploidy Level - Duchoslav, Martin; Jandová, Michaela; Kobrlová, Lucie; Šafářová, Lenka; Brus, Jan; Vojtěchová, Kateřina (Frontiers in Plant Science, 2020)
The establishment and success of polyploids are thought to often be facilitated by ecological niche differentiation from diploids. Unfortunately, most studies compared diploids and polyploids, ignoring variation in ploidy level in polyploids. To fill this gap, we performed a large-scale study of 11,163 samples from 1283 populations of the polyploid perennial geophyte Allium oleraceum with reported mixed-ploidy populations, revealed distribution ranges of cytotypes, assessed their niches and explored the pattern of niche change with increasing ploidy level. Altogether, six ploidy levels (3x–8x) were identified. The most common were pentaploids (53.6%) followed by hexaploids (22.7%) and tetraploids (21.6%). Higher cytotype diversity was found at lower latitudes than at higher latitudes (> 52o N), where only tetraploids and pentaploids occurred. We detected 17.4% of mixed-ploidy populations, usually as a combination of two, rarely of three, cytotypes. The majority of mixed-ploidy populations were found in zones of sympatry of the participating cytotypes, suggesting they have arisen through migration (secondary contact zone). Using coarse-grained variables (climate, soil), we found evidence of both niche expansion and innovation in tetraploids related to triploids, whereas higher ploidy levels showed almost zero niche expansion, but a trend of increased niche unfilling of tetraploids. Niche unfilling in higher ploidy levels was caused by a contraction of niche envelopes towards lower continentality of the climate and resulted in a gradual decrease of niche breadth and a gradual shift in niche optima. Field-recorded data indicated wide habitat breadth of tetraploids and pentaploids, but also a pattern of increasing synanthropy in higher ploidy levels. Wide niche breadth of tetra- and pentaploids might be related to their multiple origins from different environmental conditions, higher “age”, and retained sexuality, which likely preserve their adaptive potential. In contrast, other cytotypes with narrower niches are mostly asexual, probably originating from a limited range of contrasting environments. Persistence of local ploidy mixtures could be enabled by the perenniality of A. oleraceum and its prevalence of vegetative reproduction, facilitating the establishment and decreasing exclusion of minority cytotype due to its reproductive costs. Vegetative reproduction might also significantly accelerate colonisation of new areas, including recolonisation of previously glaciated areas.